In memory of Jan de Lange and Kees Hoogland: Honoring their legacy and contributions to mathematics education in Indonesia - Zulkardi; Prahmana, Rully Charitas Indra; Putri, Ratu Ilma Indra (Journal on Mathematics Education, 2025)
Inspired by the wisdom of Ali bin Abi Talib—that written legacies outlive their authors—this paper presents a scientific narrative exploring the contributions of Professor Jan de Lange (JDL) to the global and Indonesian mathematics education landscape. Renowned for his work in Realistic Mathematics Education (RME), the Trends in International Mathematics and Science Study (TIMSS), and the Programme for International Student Assessment (PISA), JDL played a pivotal role in the transformation of Indonesia’s mathematics education reform in the late 1990s. His engagement began in 1998 when, alongside Prof. Tjeerd Plomp, he responded to an invitation from Prof. R.K. Sembiring to introduce RME as an alternative to the outdated modern mathematics approach. This effort led to the birth of Pendidikan Matematika Realistik Indonesia (PMRI). The reform initiative included the selection and training of Indonesian doctoral candidates through a collaborative workshop held at Institut Teknologi Bandung (ITB), resulting in advanced studies in the Netherlands. Among these scholars was Prof. Zulkardi, who became a central figure in promoting RME and PMRI in Indonesia. JDL’s involvement continued through mentorship, keynote lectures, and academic collaborations, significantly influencing mathematics education policy and practice. His thought-provoking publications reflect his enduring commitment to curiosity-driven, student-centered learning. The paper also acknowledges the contributions of Prof. Kees Hoogland, JDL’s close colleague and fellow RME advocate. Together, their work exemplifies a vision of mathematics as meaningful, contextual, and empowering. Their legacy lives on through generations of educators and learners shaped by their transformative ideas.